The Effect of Ecoenzyme Manufacturing Practices on Improving Students' Knowledge and Attitudes Towards Organic Waste Management at the Raudlatul Firdaus Islamic Boarding School - Septa Pri Ramaja; Selviana, Selviana (Jurnal EduHealth, 2025)
Organic waste management is a challenge faced by the community, including in Islamic boarding schools. One innovative solution is the production of ecoenzymes through the fermentation of fruit and vegetable waste, which are useful as organic fertilizers, natural cleaners, and pest control. This study aims to determine the effect of ecoenzyme production practices on improving students' knowledge and attitudes in organic waste management. The research method used a quasi-experimental design with a one-group pretest-posttest design. A total of 30 students from the Raudlatul Firdaus Islamic Boarding School, Sungai Ambawang, were selected through purposive sampling. Data were obtained through questionnaires before and after the ecoenzyme production practice, then analyzed using the Wilcoxon test. The results showed a significant increase in students' knowledge (mean pretest 6.03 to 8.83; p < 0.05) and attitudes (mean pretest 33.30 to 45.60; p < 0.05) after participating in the practice. This study indicates that the ecoenzyme production practice is effective in increasing students' awareness and skills regarding organic waste management. Ecoenzyme education and training programs can be used as a sustainable strategy to support the cleanliness of Islamic boarding school environments while empowering students